2019
DOI: 10.34071/jmp.2019.5.4
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and nutritional status of cancer patients on chemotherapy

Abstract: Background: Cancer is the second cause of disease-related deaths worldwide. Malnutrition among cancer patients is very common, with an estimated incidence of approximately 40 to 80%. While it is already a proven fact that malnutrition is prevalent among cancer patients, its impact on the quality of life of patients has not been adequately studied, particularly in the local setting. Purpose: To assess quality of life, nutrition status and to determine the affects of nutrition status on quality of life of cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
1
1
Order By: Relevance
“…This result had a similarity to the studies of Qiao Sun (87.62%) and Nguyen Thi Trang (87%), but higher than Javid (41,0%) and Shpata (62.6%) (Javid Mishamandani et al, 2019; Nguyen, 2018; Qiao et al, 2020; Shpata et al, 2015). In contrast, our result was different from Nguyen Phuong Thao's study showed the percentage was 100% of patients with nutritional risk by NRS2002 (Nguyen, 2019).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This result had a similarity to the studies of Qiao Sun (87.62%) and Nguyen Thi Trang (87%), but higher than Javid (41,0%) and Shpata (62.6%) (Javid Mishamandani et al, 2019; Nguyen, 2018; Qiao et al, 2020; Shpata et al, 2015). In contrast, our result was different from Nguyen Phuong Thao's study showed the percentage was 100% of patients with nutritional risk by NRS2002 (Nguyen, 2019).…”
Section: Discussioncontrasting
confidence: 99%
“…By the seventh day, still over haft of patients had protein intake lower than 1.3 g/kg/day. This result was similar to Nguyen Phuong Thao's study carried out in Dong Da Hospital (Nguyen, 2019). Several patients received very high doses of protein (>2 g/kg/day) due to these patients being stage III and IV pressure ulcers or major burned patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation